Aging, the Medical Subspecialties, and Career Development: Where We Were, Where We Are Going. Issue 4 (16th January 2017) - Hurria, Arti; High, Kevin P.; Mody, Lona; McFarland Horne, Frances; Escobedo, Marcus; Halter, Jeffrey; Hazzard, William; Schmader, Kenneth; Klepin, Heidi; Lee, Sei; Makris, Una E.; Rich, Michael W.; et al.
Abstract : Historically, the medical subspecialties have not focused on the needs of older adults. This has changed with the implementation of initiatives to integrate geriatrics and aging research into the medical and surgical subspecialties and with the establishment of a home for internal medicine specialists within the annual American Geriatrics Society (AGS) meeting. With the support of AGS, other professional societies, philanthropies, and federal agencies, efforts to integrate geriatrics into the medical and surgical subspecialties have focused largely on training the next generation of physicians and researchers. They have engaged several subspecialties, which have followed parallel paths in integrating geriatrics and aging research. As a result of these combined efforts, there has been enormous progress in the integration of geriatrics and aging research into the medical and surgical subspecialties, and topics once considered to be geriatric concerns are becoming mainstream in medicine, but this integration remains a work in progress and will need to adapt to changes associated with healthcare reform.